2011
DOI: 10.1073/pnas.1104645108
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the function of a small GTPase RsgA on the 30S ribosomal subunit maturation revealed by cryoelectron microscopy

et al.

Abstract: The bacterial RsgA, a circularly permutated GTPase, whose GTPase activity is dependent on the 30S ribosomal subunit, is a late-stage ribosome biogenesis factor involved in the 30S subunit maturation. The role of RsgA is to release another 30S biogenesis factor, RbfA, from the mature 30S subunit in a GTP-dependent manner. Using cryoelectron microscopy, we have determined the structure of the 30S subunit bound with RsgA in the presence of GMPPNP at subnanometer resolution. In the structure, RsgA binds to the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 51 publications
9
74
2
Order By: Relevance
“…While this paper was under review another study describing the cryo-EM structure of the YjeQ in complex with the 30S ribosomal subunit was published (Guo et al 2011). …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…While this paper was under review another study describing the cryo-EM structure of the YjeQ in complex with the 30S ribosomal subunit was published (Guo et al 2011). …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Their roles in the maturation of the functional core of the 30S subunit may entail facilitating proper 17S rRNA folding, assisting processing of the rRNA, or mediating protein-RNA interactions. Cryo-electron microscopy (cryo-EM) (Sharma et al 2005;Datta et al 2007;Guo et al 2011;Jomaa et al 2011b) revealed that at least three factors, Era, YjeQ, and RbfA bind at or in close proximity to the decoding center at sites that are not overlapping, indicating that simultaneous binding is stereochemically possible. Consistently, genetic experiments (Bylund et al 1998(Bylund et al , 2001Inoue et al 2003Inoue et al , 2006Campbell and Brown 2008) suggested that these factors operate in conjunction rather than independently.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, it has been shown that YjeQ, RbfA, and Era all bind in close proximity to the decoding center of the mature 30S subunit (Sharma et al 2005;Datta et al 2007;Guo et al 2011;Jomaa et al 2011b), suggesting that these factors play a joint role in the organization of the functional core of the small subunit. Genetic evidence suggests that RimM binds to a distinct region of the head of the 30S subunit comprised of helices 31 and 33b of the 16S rRNA and r-proteins S13 and S19 right above the decoding center (Lovgren et al 2004).…”
Section: Introductionmentioning
confidence: 99%